Development of Virtual Blended Learning Based on Edmodo with Problem-Solving for Basic Physics - Kua, M Y; Dolo, F X; Suparmi, N W (Department of Physics, Faculty of Mathematics and Natural Sciences, 2022)
This research is based on the problem of changing learning patterns from face to face to online due to the COVID-19 pandemic. The objectives of this study were to develop virtual blended learning based on Edmodo with problem solving in Basic Physics courses and to describe the effectiveness of product based on trials data analysis. This research was conducted in Ngada Regency, East Nusa Tenggara province. The subjects in this study were the lecturers and students of the STKIP Citra Bakti science education study program. The measured aspect was the quality of the virtual blended learning product consists of content, presentation, and language which developed following the problem-solving learning model phase. The data obtained in this study were analyzed descriptively qualitatively to explain product quality. This product was developed with the ADDIE model proposed by Lee and Owen. The results showed that the product development had reached the evaluation stage with a mean validation score of 4.53 and was in the very good category. Otherwise, the quality of the results of the virtual blended learning trial based on problem solving from lecturers and students is in the very good category. Based on the information, developed virtual blended learning based on Edmodo with problem- solving was good to be implemented in Basic Physics courses.